DECISION SUPPORT SYSTEM FOR WEDDING PACKAGE SELECTION USING AHP AND MOORA METHODS AT ADHINATHA WEDDING ORGANIZER - Muhammad Wifqi Aufal Maulana; Anteng Widodo; Zainur Romadhon (Universitas Budi Luhur, 2026)
Wedding organizer (WO) package selection is a complex multi-criteria decision-making process that has long relied on subjective consultations. At Adhinatha Wedding Organizer, this process is still carried out manually through WhatsApp-based consultation, producing recommendations that tend to be subjective and fail to accommodate customer preferences across eight competing criteria. Previous decision support system (DSS) studies in the wedding organizer domain generally rely on a single ranking method, so results have never been cross-checked or validated by domain experts. The contribution of this research is to fill that gap by developing a web-based DSS integrating the Analytical Hierarchy Process (AHP) for criteria weighting with three ranking methods, namely Multi-Objective Optimization by Ratio Analysis (MOORA), Simple Additive Weighting (SAW), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), applied to eight criteria and thirty-six package alternatives. This research aims to design and build a web-based DSS through data collection, criteria weighting with AHP, alternative ranking, expert validation, and weight sensitivity testing. The three rankings are compared, validated against an expert consensus using Spearman correlation, and tested for stability via ±5% weight sensitivity analysis. The results show MOORA produces the ranking most consistent with expert judgment (rho = 0.998) and the most stable underweight change and is therefore selected as the system's primary ranking engine. The system is developed using the waterfall method, modeled with UML, and implemented using PHP and MySQL. It is expected to provide faster, more transparent, and more accountable package recommendations for Adhinatha Wedding Organizer customers.